Phytochemical analysis of some selected traditional medicinal plants in Ethiopia - Agidew, Misganaw Gedlu (2023)
This review of relevant medicinal plants is based on the fundamental knowledge accumulated by indigenous people of Ethiopia and to identify which types of selected medicinal plants for phytochemical analysis were analyzed and which one is not analyzed at Ethiopian levels. In this review, the most traditional medicinal plant species found and used in Ethiopia are chosen.